2018
DOI: 10.1021/acs.langmuir.8b02713
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Viscoelasticity of Highly Ordered, Two-Dimensional Assemblies of Metal Nanoparticles Confined at the Air/Water Interface

Abstract: In this study, we investigated the viscoelastic properties of metal nanoparticle monolayers at the air/water interface by dilational rheology under periodic oscillation of surface area. Au nanoparticles capped with oleylamine form a stable, dense monolayer on a Langmuir film balance. The stress response function of a nanoparticle monolayer was first analyzed using the classical Kelvin–Voigt model, yielding the spring constant and viscosity. The obtained results suggest that the monolayer of nanoparticles is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…31,32 However, interfacial elasticity is also enhanced by attractive particle interactions. 32,33 van den Berg et al 34,35 demonstrated higher interfacial elasticity for CNCs with an increasing degree of esterification, although the adsorption angle increasingly diverged from 90°. We observed a sharp increase in E′ upon salt addition beyond 10 mM NaCl, in good agreement with NaCl concentrations known to allow for CNC attractive interactions.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…31,32 However, interfacial elasticity is also enhanced by attractive particle interactions. 32,33 van den Berg et al 34,35 demonstrated higher interfacial elasticity for CNCs with an increasing degree of esterification, although the adsorption angle increasingly diverged from 90°. We observed a sharp increase in E′ upon salt addition beyond 10 mM NaCl, in good agreement with NaCl concentrations known to allow for CNC attractive interactions.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…30−32 To clarify the mechanism of the blueshift, we conducted an EDX microanalysis with HAADF-STEM imaging to investigate the size, morphology, and element distribution in QDs before and after thermal treatment. The QD-SAMs are soft compared with the self-assembled metal nanoparticles 18 because of weak van der Waals interactions between core crystals (smaller size and smaller Hamaker constants), and it was not easy to maintain the free-standing film structure on the Si 3 N 4 TEM grid. In addition, the damage to the organic ligands under the high-power electron beam of the HAADF-STEM system was unavoidable, so the images obtained were blurry, and the elemental line scan was noisy; however, we could still obtain several pieces of important information.…”
Section: Mechanism Of Emission Color Changementioning
confidence: 99%
“…Over the past decade, our group has been studying the self-assembly of metal nanoparticles at the centimeter scale to create plasmonic metasurfaces or metamaterials, utilizing the Langmuir–Schaefer (LS) method (transferring of a self-assembled film formed at the air–water interface by stamping). This technique is well established for molecular assembly, but is not as widely employed for nanomaterials not only because of the difficulty of obtaining a hexagonally packed local structure but also the difficulty of controlling the viscoelastic properties of the film to realize a homogeneous and continuous film in centimeter-scale through a compression process . The interaction between ligand molecules and metal cores determines not only the local packing structure but also the plasticity of the film.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure S5 we confirmed that the fitting up to the 5th mode was sufficient. Following our previous accounts [34,35] we focus first on the linear contribution and thus analyze only the phase separation and viscoelastic moduli obtained from the first mode (indicated by the index 1) of the Fourier series expansion, which represents~89 % of the signal. [36,37] As presented in Figure S6, the phase separation between stress and strain exhibits a minor increase from ϕ 1 � 0.2 to 0.6 following the increase in the strain frequency from f = 1 mHz to 150 mHz.…”
Section: Figurementioning
confidence: 99%